Environment, Trade and Society in Southeast Asia - Henley, D. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2015)
This title is available online in its entirety in Open Access. In Environment, Trade and Society in Southeast Asia: A Longue Dur